2019
DOI: 10.21037/jtd.2019.06.44
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of CD206+CD14+ macrophages in diagnosis of lung cancer originated malignant pleural effusion

Abstract: Background: Pleural effusions are common complications of various diseases. Patients with malignant pleural effusion (MPE) usually face poor prognosis and short life expectancy. Discriminating between MPE and benign pleural effusion remains to be difficult. The aim of our current study was to evaluate whether CD206 + CD14 + macrophages could be a diagnostic biomarker for MPE. Methods: The percentages of CD14 + , CD86 + CD14 + and CD206 + CD14 + macrophages in pleural effusions were determined by flow cytometry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 26 publications
2
4
0
Order By: Relevance
“…Macrophages are one type of main immune cells infiltrating into MPE and present a wide range of M1/M2 spectrum ( 31 ). Consistent with previous studies ( 32 34 ), our present study confirmed that macrophages in MPE were characterized by M2-polarized phenotype. Although the immunoregulatory function of macrophages have been illustrated in most tumor models, the underlying role of macrophages in MPE remains to be clarified.…”
Section: Discussionsupporting
confidence: 93%
“…Macrophages are one type of main immune cells infiltrating into MPE and present a wide range of M1/M2 spectrum ( 31 ). Consistent with previous studies ( 32 34 ), our present study confirmed that macrophages in MPE were characterized by M2-polarized phenotype. Although the immunoregulatory function of macrophages have been illustrated in most tumor models, the underlying role of macrophages in MPE remains to be clarified.…”
Section: Discussionsupporting
confidence: 93%
“…1C). When Mφs, which are known to accumulate in MPE ( 16 ), ingest apoptotic cells, they are educated to acquire an anti- inflammatory phenotype, often associated with a protumorigenic function ( 17 ). However, whether clearance of apoptotic cells by Mφs, rather than a direct mechanism of cancer cell immune evasion, controls MPE progression has not yet been tested.…”
Section: Resultsmentioning
confidence: 99%
“…At a threshold of 3.65%, the diagnostic sensitivity and specificity of CD14 + D163 + macrophages were 0.86 and 1.00, respectively (82). In another study, the authors investigated the diagnostic accuracy of CD206 + CD14 + macrophages for lung cancer-induced MPE (83), reporting an AUC as high as 0.98, with 0.88 sensitivity and 1.00 specificity at a 39.8% threshold.…”
Section: Tumor-associated Macrophages (Tams) and Monocytesmentioning
confidence: 99%